Dipeptidyl Peptidases as Survival Factors in Ewing Sarcoma Family of Tumors: IMPLICATIONS FOR TUMOR BIOLOGY AND THERAPY - Lu, Congyi (American Society for Biochemistry and Molecular Biology, 2011)
Ewing sarcoma family of tumors (ESFT) is a group of aggressive pediatric malignancies driven by the EWS-FLI1 fusion protein, an aberrant transcription factor up-regulating specific target genes, such as neuropeptide Y (NPY) and its Y1 and Y5 receptors (Y5Rs). Previously, we have shown that both exogenous NPY and endogenous NPY stimulate ESFT cell death via its Y1 and Y5Rs. Here, we demonstrate that this effect is prevented by dipeptidyl peptidases (DPPs), which cleave NPY to its shorter form, NPY(3–36), not active at Y1Rs. We have shown that NPY-induced cell death can be abolished by overexpression of DPPs and enhanced by their down-regulation. Both NPY treatment and DPP blockade activated the same cell death pathway mediated by poly(ADP-ribose) polymerase (PARP-1) and apoptosis-inducing factor (AIF). Moreover, the decrease in cell survival induced by DPP inhibition was blocked by Y1 and Y5R antagonists, confirming its dependence on endogenous NPY. Interestingly, similar levels of NPY-driven cell death were achieved by blocking membrane DPPIV and cytosolic DPP8 and DPP9. Thus, this is the first evidence of these intracellular DPPs cleaving releasable peptides, such as NPY, in live cells. In contrast, another membrane DPP, fibroblast activation protein (FAP), did not affect NPY actions. In conclusion, DPPs act as survival factors for ESFT cells and protect them from cell death induced by endogenous NPY. This is the first demonstration that intracellular DPPs are involved in regulation of ESFT growth and may become potential therapeutic targets for these tumors.